Effects of Multiple Pregnancies on Mother and Foetus (KYAMC Journal, 2022)
Background: The incidence of multiple pregnancies is on rising due to a variety of reasons like increased use of assisted reproductive techniques and an increasing number of women having a pregnancy at an advanced age. A mother with twin pregnancy needs to be taken under the special care category.Objectives: We are intended to observe the effects associated with twin or higher-order pregnancy.Materials and Methods: This is a descriptive type of cross-sectional observational study conducted in the Department of Gynae and Obstetrics, Bangabandhu Sheik Mujib Medical University and Dhaka medical college hospital over a period of six months from 1st July to 31st December 2014. Total fifty patients were included in the study. Inclusion criteria were pregnant women who would be admitted with multiple pregnancies in BSMMU & DMCH.Results: Average age of the responding patients was 24.54 years with standard deviation of ±3.93. Forty-two (84%) patients had ANC. Maximum (34%) patients had no complication, 8(16%) patients had GDM, 8(16%) patients had Preterm labor (PTL), 12 (24%) patients had Preeclampsia and only 5(10%) patients had PROM. Maximum (50%) babies had no significant fetal outcome, 30% babies had low birth weight, 16% babies were very low birth weight and 4(8%) patients had fetal demise.Conclusion: Now a days the incidence of multiple pregnancies is increasing due to ART. Multiple pregnancies are high-risk pregnancies with more complications in comparison to a single pregnancy. Our study reveals that nearly half of the cases had no maternal or fetal complication, Commonest maternal complications were preterm labor, Premature rupture of membranes (PROM), preeclampsia, and fetal outcomes were premature and low birthweight babies.KYAMC Journal. 2022;12(04): 196-199